(untitled) (Medico Legal Update, 2021)
One hundred and ten samples of the tap water in Baquba city were collection .Ten isolates were obtained. The results of the sensitivity test showed that 10 isolates were multidrug, 10 isolates exhibited moderate resistance ranging from 5-8 antagonists. Through the use of the RAPD-PCR profiling system, the vast majority of Escherichia coli strains under study have large genomes and high virulence factors by belonging to group A2. Results of genetic profiling using the ERIC- PCR and BOX-PCR system showed several groups of isolates were identified as having a genetic variation and B2 group was given the highest proportion of ERIC- PCR system,70% in ERIC While A2 group was given the highest proportion of BOX- PCR system,40% in the BOX indicating that there is a negative spread The present study indicates that there is a correlation between taxonomic systems was evident by the distribution of isolates in each pattern and group.